Synergistic Integration of Chemically Modified Graphene and Silver Nanoparticles for Highly Sensitive Acetylcholinesterase-Based Biosensors in Pesticide Detection - Yashwant, Dr. Khire Mohan; Deshmukh, Dr. Shailesh Madhavrao (Migration Letters, 2023)
Biosensors have become indispensable instruments in modern analytical research, with the opportunity to significantly transform diverse domains such as environmental monitoring and food safety. This study aims to discuss the urgent need for precise and reliable pesticide detection, focusing on the difficulties encountered by current methodologies. Pesticides serve a crucial function in agriculture, although their residues pose significant risks to human health and the environment if they exceed the established thresholds. The existing detection techniques often encounter sensitivity and selectivity challenges, necessitating the exploration of more sophisticated strategies. Given these obstacles, this research provides a unique Nanoparticle-based Biosensors Design for Pesticide Detection (NP-BSD-PD) approach. The proposed methodology integrates chemically modified graphene and silver nanoparticles, leveraging their distinctive characteristics to augment the sensitivity and accuracy of pesticide detection. The technology utilizes biosensors based on acetylcholinesterase, enabling the detection of trace levels with high sensitivity. The experimental research yielded findings indicating that NP-BSD-PD exhibited exceptional performance across several parameters. The technique has remarkable sensitivity and accuracy, as shown by the Zeta Potential of -24.89 mV, pH of 7.4, Voltage of 2.7 V, Current of 48.89 µA, Inhibition Percentage of 88.56%, and a Detection Limit of 0.3 ng/mL. The results highlight the potential of NP-BSD-PD as a viable technique for detecting pesticides. This method effectively addresses significant limitations present in existing approaches, facilitating advancements in food safety and environmental preservation.